RELASI TEKSTUALITAS TAFSIR DAN SIKAP KEBERAGAMAAN - Muhammad Azizan Fitriana; Husnul Maab (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2023)
In general, this article describes the textual approach which has been considered as a counter-productive entity in understanding the Qur’an. This is because the ‘textuality of interpretation’ that has been carried by certain religious groups offers one concept: ‘one side truth claim’, unilateral truth. In this textual lens the interpretation of certain verse in the Qur’an looks very rigid, even touching the realm of extremism, both hard exxtrimsm (phsyical violence) and sof extremism (verbal or disourse violence). The vocabulary of Shirk, hypocrite, infidel is very familiar to hear from approaches that rely only on this textia; dimension. Resonance of these kinds of stimas is not only to respond to practices that are not agreed upon; but also to respond to national and state issues. The context of this kind of approach is of course very incompatible i fit has to be brought and applied to Indonesia’s climate which has a plural face. Therefore, as the anti-thesis of this group, there is also a group that offers a contextual approach to understanding Qur’an. the contextual approach is deemed appropriate and suitable considering the spirit contained in the Qur’an is ‘shalih likulli zaman wa makan’, relevant to every time and place. Therefore approaching the Qur’an with the spirit of its time cannot bi avoided, it is even felt to be very crusial, especially for religious communities. A person’s face or way of religion really depends on how he understand the basic sources of his teaching; Qur’an. Therefore, this research will further elaborate on these two approaches, especially, the textual approach in order to find out how relevant and what influences it has. To achive this, this research utilize the method of library research with a desriprive-analytical-crytical approach as an instrument to find objective data in viewing this reality.